2017
DOI: 10.1093/ijpor/edx016
|View full text |Cite
|
Sign up to set email alerts
|

Personal Issue Importance and Motivated-Reasoning Goals for Pro- and Counterattitudinal Exposure: A Moderated Mediation Model of Motivations and Information Selectivity on Elaborative Reasoning

Abstract: This study draws on an experiment combined with Web behavior-tracking data to understand the roles of intrinsic and extrinsic motivations, including personal issue importance and motivated-reasoning goals, in influencing people to seek pro-and counterattitudinal information and how this information selectivity in turn affects elaborative reasoning. Findings suggest that proattitudinal exposure mediates the relationship between personal issue importance and generating rationales for one's own viewpoint on the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Exposure to counterattitudinal viewpoints is essential to reasoned public opinion and deliberative democracy (Habermas, 1989). Scholars have found that exposure to counterattitudinal viewpoints not only facilitates political tolerance, informed opinion, and a better understanding of a political issue, but it also leads to political ambivalence that makes people uncertain of their own positions and further discourages them from political engagement (Chen, 2017;Mutz, 2002aMutz, , 2002b.…”
Section: The Moderating Role Of Disagreement and Publicness In The Nementioning
confidence: 99%
“…Exposure to counterattitudinal viewpoints is essential to reasoned public opinion and deliberative democracy (Habermas, 1989). Scholars have found that exposure to counterattitudinal viewpoints not only facilitates political tolerance, informed opinion, and a better understanding of a political issue, but it also leads to political ambivalence that makes people uncertain of their own positions and further discourages them from political engagement (Chen, 2017;Mutz, 2002aMutz, , 2002b.…”
Section: The Moderating Role Of Disagreement and Publicness In The Nementioning
confidence: 99%
“…There are a number of potential sources of variability in interest and information seeking. A number of studies suggest that those high in need for cognition, or who are higher in motivation, may be inclined to seek out a wider range of media on a given subject, may be more inclined to seek detail, and may acquire a more accurate understanding of risk (see Chen, 2018;Dvir-Gvirsman, 2015;Jung et al, 2020;Wei et al, 2007Wei et al, , 2010Wei et al, , 2015. Similarly, research on dual process models of information processing, such as the heuristic systematic model (Eagly & Chaiken, 1993), would suggest that people will continue to seek information until they reach some level of information sufficiency, whereby they feel that they can make successful decisions (Kahlor, 2007;ter Huurne, Griffin, & Gutteling, 2009;Yang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…For example, second screening can be used to pay attention to a specific political issue. Thus, the model can be examined to understand issue publics and their issue specificity (Chen, 2018a; Kim, 2009). The model can also be extended to explore more indirect and conditional effects (Valkenburg & Peter, 2013).…”
Section: Discussionmentioning
confidence: 99%